Physico-chemical investigation of wastewater from the Sebdou-Tlemcen textile complex North-West Algeria - Asma Khelassi- Sefaoui; Abderrahmane Khechekhouche; Manel Zaoui-Djelloul Daouadji; Hamza Idrici (Indonesian Journal of Science and Technology, 2021)
Wastewater treatment is a process used in several countries, particularly in Algeria. A study on Earth for one month was carried out at the sewage plant of the Sebdou textile complex, Tlemcen, north-west of Algeria. Regular samples gave average values at the outlet such that the water temperature is 22 ° C, the ph 7.43, the biochemical oxygen demand BOD5 is 36.5 mg / l, the chemical oxygen demand COD vary between 100 and 200 mg / l at the exit of the WWTP mg / l and finally suspended solids SS is of the order of 36.2 mg / l. All these values conform with the standards and therefore the treatment plant operates within Algerian standards.